Strict Joint and Several Liability and Justice - Cooley, D. R. (Journal of business ethics, 2003)
The American tort system regularly conducts a sort of lottery in which plaintiffs try to name as many defendants in a tort action as they can in order to collect a large judgment from at least one of them. This procedure is encouraged under strict joint and several liability, which permits plaintiffs to recover greater damages from defendants – usually businesses – with less moral culpability for the tort than poorer defendants, who bear greater culpability. In a case involving the Disney Corporation and a negligent amusement park rider, for instance, Disney was forced to pay 86% of the court award to the plaintiff, even though the jury found the company to be only 1% liable for the injury. The legal principle of joint and several liability violates morality in several different ways. Even though the principle appears to be better in the short run for plaintiffs, I will show that it fails not only to satisfy utilitarianism, but compensatory justice as well. Hence, the legal principle of joint and several liability should be eliminated in favor of a better, fairer law, which I will briefly sketch at the end.